The dust content of QSO hosts at high redshift. Issue 4 (25th January 2014) - Calura, F.; Gilli, R.; Vignali, C.; Pozzi, F.; Pipino, A.; Matteucci, F.
Abstract: Infrared observations of high- z quasar (QSO) hosts indicate the presence of large masses of dust in the early Universe. When combined with other observables, such as neutral gas masses and star formation rates, the dust content of z ∼ 6 QSO hosts may help constraining their star formation history. We have collected a data base of 58 sources from the literature discovered by various surveys and observed in the far-infrared. We have interpreted the available data by means of chemical evolution models for forming protospheroids, investigating the role of the major parameters regulating star formation and dust production. For a few systems, given the derived small dynamical masses, the observed dust content can be explained only by assuming a top-heavy initial mass function, an enhanced star formation efficiency and an increased rate of dust accretion. However, the possibility that, for some systems, the dynamical mass has been underestimated cannot be excluded. If this were the case, the dust mass can be accounted for by standard model assumptions. We provide predictions regarding the abundance of the descendants of QSO hosts; albeit rare, such systems should be present and detectable by future deep surveys such as Euclid already at z > 4.